Legal Review of Traffic Accidents Resulting in Death - Sari, Panji Prasetyo; Arpangi, Arpangi (UNISSULA Semarang, 2025)
Traffic accidents often occur in various places throughout Indonesia. Traffic accident victims are of several groups, whether minor, severe, or death. In this study, the author would like to describe the legal review of traffic accidents that result in fatalities. In this study, the approach method used is: sociological legal approach or approach by direct review in the field. The research specification used is Analytical Descriptive, which is an effort to analyze and explain legal problems related to objects with a comprehensive and systematic description of all matters related to the legal review of traffic accidents resulting in fatalities. The author believes that it is important to enforce and protect the law against victims and perpetrators who experience traffic accidents. This aims to ensure that victims and perpetrators are processed in accordance with applicable laws and receive their rights accordingly.